Rasch Analysis: Students' Mathematics Anxiety and Symptoms - Rahmita Sonia; Alizamar Alizamar; Alwen Bentri; Febri Wandha Putra (Jurnal Aplikasi IPTEK Indonesia, 2020)
Ideally students follow mathematics learning effectively without any disturbance. But the phenomenon that is happening is that there are students who experience anxiety about mathematics, which causes students to not be able to follow mathematics learning effectively. The purpose of this study is to describe the level of mathematics anxiety experienced by students as a whole and also based on the aspects studied. This study involved 32 students in class XII consisting of 18 female students and 14 male students. The instrument  used in this research in the form of a questionnaire containing statements about mathematical anxiety equipped with a Likert scale model. Data analysis using frequency distribution techniques and Rasch Model analysis. The results of the analysis of research data indicate that some students experience mathematical anxiety. In addition, the results of data analysis also showed that there were differences in anxiety between female students and male students both overall and based on aspects of the mathematics anxiety studied.